2011
DOI: 10.1159/000322361
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Volume and Its Correlation with Histopathological Outcomes in Prostate Cancer

Abstract: Introduction: There is a paucity of data investigating the relationship between histopathological variables of oncologic importance and prostate volume, and we aimed to investigate this. Patients and Methods: 2,207 consecutive patients who underwent robotic-assisted radical prostatectomy were studied. Preoperative demographic and both pre- and postoperative histopathological parameters were compared among the small (<40 cm3), intermediate (40–70 cm3), and large (>70 cm3) prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Several studies have shown a lower rate of PSM in patients with larger prostates . Confirmingly, we saw a trend towards lower PSM in patients with larger glands, however this finding was not significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have shown a lower rate of PSM in patients with larger prostates . Confirmingly, we saw a trend towards lower PSM in patients with larger glands, however this finding was not significant.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies confirmed these results . Smaller glands showed higher percentage of cancer than larger ones . This might favour an infiltration of the capsule and lead to a higher rate of PSM and ECE and can lead to a worse BCR‐free survival.…”
Section: Discussionmentioning
confidence: 99%
“…reported that men with smaller prostates had larger tumor volumes, were less organ confined, had more EPE, and experienced more biochemical recurrence. Sooriakumaran et al 30. found that small prostate volume had a higher rate of PSM in patients undergoing RP.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst larger prostates present a technical challenge at robotic prostatectomy and are associated with a longer operative time [ 6 ], greater blood loss, and increased postoperative complications [ 3 , 7 ], they are associated with a superior oncological outcome in terms of reduced extraprostatic disease, reduced positive margin rate [ 8 14 ], and decreased biochemical recurrence rate [ 3 ]. In this cohort there was no significant difference between larger prostates (≥75 g) and smaller prostates (<75 g) in terms of the preoperative staging; however, the two groups were markedly different postoperatively.…”
Section: Discussionmentioning
confidence: 99%